Analisis Penerapan Three Poin Light Pada Program Podcast Helmy Yahya Bicara Episode Invasi Rusia – Ukraina Akankah Menyulut PD - III - Abdul Hakim (Program Studi Ilmu Komunikasi, 2022)
Podcast is a program that is starting to be liked by the public, because there is a lot of information that can be obtained from each episode that is aired, one of which is Helmy Yahya's podcast Talking with the episode of Invasion of Russia – Ukraine, will it spark WWIII?. The episode presented a resource person, a military observer, Mrs. Connie Rakahundini Bakrie. Proper lighting on a podcast show is an important part of producing a clear, noise-free and attractive image that is comfortable for viewers to see. Through a qualitative descriptive approach, research and analysis were carried out on the application of Three Points Light lighting, especially on blocking Key light; Fill Light and Back Light on Helmy Yahya's podcast Talk, episode The Invasion of Russia – Ukraine will ignite to World War III ?. The results of observations and analysis of several shots show that lighting techniques have not been applied properly. This has affected the image quality and could affect the viewer's comfort.